A prescription for primary nozzle diameters for solar driven ejectors. (May 2015) - Dennis, M.; Cochrane, T.; Marina, A.
Highlights: Conventional solar driven ejectors have low cooling yield due to fixed geometry. Ejectors with variable geometry must respond to varying solar irradiance and ambient temperature. The ejector primary nozzle position and throat diameter must be actuated. For efficient mixing, the nozzle exit diameter should also be actuated. A prescription is provided to determine the ejector nozzle diameters. Abstract: There is a growing interest in ejector cooling systems driven by solar heat. One of the main problems with solar cooling using ejectors is that the ejector cannot operate well if the operating conditions stray from the design point temperatures. Ejectors with variable geometry have been proposed and modelling shows that they are able to increase the operating range of an ejector. In particular, ejectors with a variable primary nozzle throat diameter have been experimentally shown to enhance ejector performance. This paper extends the work of others to provide a means to design a primary nozzle with variable throat diameter and variable nozzle exit diameter. The algorithm is extended to account for the behaviour of the solar collector and vapour generator. In this way, the nozzle diameters are determined as a function of the operating conditions ambient temperature and solar radiation. This correlation provides the basis for a practical nozzle control system.